“Comply or Goodbye” : Representations of Women in the Red Pill Discourse on Instagram - Levy, Emmi (My University, 2021)
This thesis examines the representations of women in a dataset collected from Instagram accounts that explicitly support the Red Pill ideology. The Red Pill is a prevailing ideology within various antifeminist groups that aims to reveal the true nature of feminism: according to the Red Pill, feminism is an oppressive system generated to subdue men, and consequently, the ideology provides advice for men to navigate within this oppression. The objective of this study is to investigate the shared social cognitions of women within the Red Pill community and see how they are connected to the Red Pill ideology. The study also aims to connect the analysed discourse to the wider social context, by exploring the growing phenomena of online misogyny and linking the findings to other virtual domains where misogyny is mediated. The analysis is based on the principles of critical discourse analysis, and the main method that is used for analysing the data is van Dijk’s sociocognitive approach (2001), which allows the investigation of shared social cognition of a community as well as the examination of personal mental models of individuals. The results of the analysis indicate that the Red Pill discourse on Instagram reproduces negative and even hostile representations of women and uses various strategies to generate the image of women as inferior. In addition, the results suggested that the Red Pill discourse on Instagram is softer and subtler in nature, compared to other anti-feminist online domains. The study also addressed the negative implications of sexist discourses and established that resentment towards women can be initiated by various factors, like women occupying domains formerly dominated by men, or it can be rooted in particular political stances. Antifeminist attitudes can also be sparked as a counteract for recent popularity of feminism and progressive politics. Regardless of the root cause, antifeminism can have severe consequences, and therefore online domains, especially popular social media platforms ought to address this issue.
Keywords: sexist discourse, antifeminism, Red Pill ideology, Manosphere, Instagram, sociocognitive approach, critical discourse analysis